(untitled) (Annals of Medical Research, 2023)
Aim: We aimed to show whether liver and renal function tests impairment have an effect on cardiovascular major adverse events (MACE) in patients with chronic heart failure (CHF). Materials and Method: 514 Patients with Ejection Fraction (EF) <40% were screened retrospectively. Biochemical and hemogram parameters of the patients at the first admission were recorded. GFRs were calculated with the MDRD formula. Patients were classified into four groups based on whether they had just a kidney injury, only a liver damage, both a kidney and liver injury, or neither a kidney and liver injury. Exitus, stroke, and hospitalization were taken as major cardiovascular adverse events, and whether they had a major cardiovascular adverse event within one year was recorded. Results: There was no difference between the groups in terms of exitus. When the groups were compared, a difference was found between the groups in terms of stroke, hospitalization, and MACE rates (p=0.001; p= 0.017; p=0.004, respectively). Stroke rate (13.8%) in the only kidney injury group; hospitalization (24%) and MACE (38%) in the liver + kidney injury group were found. As a result of binary logistic regression analysis, it was found that creatinine and EF predicted hospitalization for CHF, stroke, and MACE. Conclusion: In heart failure patients, the rate of stroke was higher in the group with only kidney injury, and the rates of hospitalization and MACE were higher in the group with both liver and kidney injury. It was found that creatinine and EF predicted hospitalization, stroke, and MACE from CHF.